2022
DOI: 10.1177/00034894221078365
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin A in the Management of Pediatric Sialorrhea: A Systematic Review

Abstract: Objective: Botulinum toxin A is known to be effective and safe in managing sialorrhea in pediatric patients; however, there is no consensus on a protocol for optimal injection sites and appropriate dosing for injection. Methods: This review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocol. PubMed, EMBASE, and other databases were queried to identify articles that evaluated botulinum toxin type A for the treatment of sialorrhea in the pediatric population. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“… 43 Diffusion of toxin into adjacent musculature can cause chewing difficulties and transient weakness of mouth closure; however, this is less common with ultrasound guidance for injection. 44 Due to the severe sialorrhea status of our patients, reasonable dose, and our accurate way to locate salivary glands, we have not found the side effects.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“… 43 Diffusion of toxin into adjacent musculature can cause chewing difficulties and transient weakness of mouth closure; however, this is less common with ultrasound guidance for injection. 44 Due to the severe sialorrhea status of our patients, reasonable dose, and our accurate way to locate salivary glands, we have not found the side effects.…”
Section: Discussionmentioning
confidence: 85%
“…The side effect profiles of neurotoxin injections are generally fewer and more tolerable than anticholinergic medication, including dry mouth, saliva thickening, and salivary gland swelling 43 . Diffusion of toxin into adjacent musculature can cause chewing difficulties and transient weakness of mouth closure; however, this is less common with ultrasound guidance for injection 44 . Due to the severe sialorrhea status of our patients, reasonable dose, and our accurate way to locate salivary glands, we have not found the side effects.…”
Section: Discussionmentioning
confidence: 99%
“…These uncommon systemic effects, however, are only observed in people with underlying medical problems or at extremely high dosages. In a recent systematic review, Heikel et al [33] evaluated the impact of BoNT treatment in the management of pediatric sialorrhea. Adverse occurrences included speech problems, dysphagia, and dysarthria ranging from mild to moderate.…”
Section: Discussionmentioning
confidence: 99%
“…While adverse events related to BoNT injections are rare, it is noteworthy that severe dysphagia can occur in children, leading to compromised food and fluid intake, as well as weight loss. Additionally, xerostomia, dysarthria, speech difficulties, coughing, and feeding difficulties have been reported, along with instances of saliva thickening and weakening of the oral musculature [ 28 ]. In the study by Yu et al, among adults, adverse events were reported in 7 out of 12 trials.…”
Section: Clinical Use Of Bontsmentioning
confidence: 99%